AIDA DALAM DIGITAL MARKETING COMMUNICATION LEMBAGA AMIL ZAKAT NASIONAL DOMPET DHUAFA - Arina Muntazah; Rosiana Andhikasari (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2021)
This study is purposed to analyse the AIDA strategy model (Attention, Interest, Desire and Action) in digital marketing communication strategies at Laznas Dompet Dhuafa. In this study, a qualitative approach was used with a descriptive study research method. The results showed that AIDA became the model applied by Laznas Dompet Dhuafa in planning and developing digital communication marketing strategies, with the use of digital media websites and social media to attract attention (attention), give an attractive impression (interest), make potential donors have a desire (desire) to donate and make potential donors take decisions (action) to donate at Laznas Dompet Dhuafa.